ISOLATION AND CHARACTERIZATION OF BIOFILM FORMING ESCHERICHIA COLI FROM CHICKEN MEAT SAMPLES - I. Manikkavasagan; K. Vijayarani; B. Murugan; S. Meignanalakshmi; S. Eswari (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was aimed to investigate the presence of Escherichia coli (E.coli) in raw chicken meat samples collected from retail shops, as well as the biofilm-forming ability of field isolates, and to characterize different adhesion genes. Out of 20 chicken meat samples, 17 (85%) were positive for E. coli. Fifteen E. coli strains were characterized by PCR using the 16S rDNA primers and all the isolates were positive which confirmed that all the isolates were E.coli. Out of the 15 confirmed E.coli field isolates which were subjected to biofilm-forming assay, 46% of them were found to be strong biofilm producers. While all the isolates were screened for the presence of adhesion genes viz. luxS, csgA, fimH, fimA, and papC, the adhesion gene luxS was detected in all the strains (100%). The other adhesion genes csgA, fimH and fimA were detected in 93%, 93%, and 73% of the isolates, respectively. The E. coli field isolates were screened blaTEM gene was detected in only four strains, which was categorized under strong biofilm producers. This study demonstrated the presence of biofilm forming E. coli in the raw chicken meat samples as contaminants, causing spoilage and potentially posing risk to consumer’s health and safety.